The ratio adipsin/MCP-1 is strongly associated with structural changes and CRP/MCP-1 with symptoms in obese knee osteoarthritis subjects: data from the Osteoarthritis Initiative. Issue 8 (August 2019) - Martel-Pelletier, J.; Tardif, G.; Rousseau Trépanier, J.; Abram, F.; Dorais, M.; Raynauld, J.-P.; Pelletier, J.-P.
Summary: Objective: There is a need to identify reliable biomarkers that can predict knee osteoarthritis (OA) progression. We investigated a panel of adipokines and some related inflammatory factors alone and their ratios for their associative value at assessing cartilage volume loss over time and symptoms in obese [High body mass index (BMI)] and non-obese (Low BMI) OA subjects. Design: Human OA serum was from the Osteoarthritis Initiative Progression subcohort. Baseline levels of adiponectin (high and low molecular weight forms), adipsin, chemerin, leptin, visfatin, C-reactive protein (CRP), interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) were evaluated with specific assays. Cartilage volume was assessed at baseline and 48 months by quantitative magnetic resonance imaging (MRI), and symptoms using baseline Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores. Data were analysed by linear regression with confounding factors at baseline, followed by multiple comparison adjustment. Results: The levels of the nine biomarkers and their ratios (36) were studied. Among High BMI subjects, only the ratio adipsin/MCP-1 was associated with cartilage volume loss over time in the lateral compartment [ β,  −2.95; 95% confidence interval (CI),  −4.42,  −1.49; P  = 0.010], whereas MCP-1 was associated with WOMAC pain (−1.74; −2.75,  −0.73; P  = 0.030) and the ratio CRP/MCP-1 with WOMAC pain (0.76; 0.37, 1.14; P  = 0.023), function (2.43; 1.20, 3.67; P  = 0.020) and total (3.29; 1.58, 5.00; P  = 0.027). No associations were found for biomarkers or ratios in Low BMI OA. Conclusion: In this study, the ratio adipsin/MCP-1 was found to be associated with the knee structural changes and that of CRP/MCP-1 with symptoms in obese OA subjects. Our data further underline the relevance of ratios as biomarkers to a stronger association to OA progression and symptoms.